Novel reversibly switchable wettability of superhydrophobic–superhydrophilic surfaces induced by charge injection and heating - Ye, Xiangdong; Hou, Junwen; Cai, Dongbao (Beilstein Journal of Nanotechnology, 2019)
Reversibly switching wettability between superhydrophobicity and superhydrophilicity has attracted widespread interest because of its important applications. In this work, we propose a reversible superhydrophobic–superhydrophilic conversion induced by charge injection and heating. Different from the conventional electrowetting phenomenon caused by the accumulation of solid–liquid interfacial charges, we discovered a phenomenon where charge injection and accumulation at the solid surface results in a sharp increase in wettability. The wettability of a sprayed SiO2 nanoparticle coating on a glass slide was shown to change from superhydrophobic to superhydrophilic by charge injection and heating, and the superhydrophobicity was restored by heating, verifying a reversible superhydrophobic–superhydrophilic conversion. The influence of voltage, temperature, and time on the coating wettability and its durability under reversible conversion have been studied.
Keywords: charge injection; heating; reversible wettability; superhydrophilic; superhydrophobic